(untitled) (Quinto Sol, 2018)
In the context of the creation of the Day of Tradition in the province of Buenos Aires, which was set up for the first time in 1939 and in its further nationalization, discourses circulated as to the gaucho affiliation with the so called “argentinidad” (Argentinity). Reporters and historians sketched a variety of interpretations that were rapidly retorted by traditionalists and public officials. This article explores an underestimated perspective in the studies on the gaucho consecration as national symbol: the dissenting voices that argued this belief, to point out who placed at the forefront of the desecration (demystification) of the gaucho; on what grounds the qualification of “gauchophobic” was sustained; what were the limits that those narratives shows; how they affect the extent of the “Argentine gaucho tradition” consensus; and what alternatives were proposed against the confirmation of the gaucho as “national type”. The latter queries are some of the guidelines intended to unveil in the development of this work. Conferences, written publications, newspaper columns, private correspondence and vindication literature promoted from traditionalist spheres allow a thorough analysis of these disputes.